2021
DOI: 10.1021/acs.chemrestox.0c00450
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Metabolites from Thiazole-Containing Drugs: Quantum Chemical Insights into Biotransformation and Toxicity

Abstract: Drugs containing thiazole and aminothiazole groups are known to generate reactive metabolites (RMs) catalyzed by cytochrome P450s (CYPs). These RMs can covalently modify essential cellular macromolecules and lead to toxicity and induce idiosyncratic adverse drug reactions. Molecular docking and quantum chemical hybrid DFT study were carried out to explore the molecular mechanisms involved in the biotransformation of thiazole (TZ) and aminothiazole (ATZ) groups leading to RM epoxide, S-oxide, N-oxide, and oxazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…Despite its apparent success, 2-AMT is considered very problematic for drug design due to often observed unspecific reactivity or promiscuous behavior. The presence of sulfur infers the possibility of undesirable interactions with the GSH system or unwanted biotransformation, e.g., S-oxidation or oxidative ring openings [ 12 , 13 ]. As a consequence, several 2-AMT-containing groups are currently categorized as PAINS and thus often disqualified in the discovery of new chemical entities [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its apparent success, 2-AMT is considered very problematic for drug design due to often observed unspecific reactivity or promiscuous behavior. The presence of sulfur infers the possibility of undesirable interactions with the GSH system or unwanted biotransformation, e.g., S-oxidation or oxidative ring openings [ 12 , 13 ]. As a consequence, several 2-AMT-containing groups are currently categorized as PAINS and thus often disqualified in the discovery of new chemical entities [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ω value of 5‐PC is close to that of thioamide, which indicates that nucleophilic residues or GSH can attack at C5 position of 5‐PC and generate adducts. [ 28 ] The ω values of 5‐PC and thioamide generated by sudoxicam are higher than that of meloxicam, which may be one of the reasons for the different toxicity of the two drugs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19–23 ] Cpd I has two closely exposed spin states (S = 3/2 and S = 1/2), so the metabolic pathways were studied with high spin (HS) and low spin (LS) state Cpd I. [ 19,24–26 ] The electrophilicity analysis [ 27,28 ] is useful in estimating the toxicities of important reactive metabolites. Chemical hardness ( η ) shown in equation ( η = ε HOMO − ε LUMO ) is a useful global index of reactivity in atoms, molecules, and clusters, where ε HOMO and ε LUMO are the energies of highest occupied molecular orbitals (HOMOs) and lowest unoccupied molecular orbitals (LOMOs), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…15 The biochemical transformation results in the generation of metabolites/intermediates with chemical reactivity, which initiates the varieties of toxicities. 16 Quinone methides are often reported to be reactive metabolites formed via oxidation and elimination reactions. 17 Phenolic derivatives or phenolic structures, such as 4-trifluoromethylphenol and phencyclidine compounds, can be oxidized to reactive intermediates with a quinone methide structure, leading to liver damage or even death.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, increasing studies have demonstrated that biotransformation also can induce toxicities . The biochemical transformation results in the generation of metabolites/intermediates with chemical reactivity, which initiates the varieties of toxicities . Quinone methides are often reported to be reactive metabolites formed via oxidation and elimination reactions .…”
Section: Introductionmentioning
confidence: 99%